Moral Equality and Human Rights: Considerations of Equality for the 21st Century - Arroyo, Lorenzo. (Tufts Archival Research Center, 2005)
This paper is an attempt to supplement our list of human rights proper with a new consideration: the right of each person to treatment as a moral equal. The ethical tenet of moral equality is powerful since it identifies wrongs that are often difficult to name and supports other core human rights. Although there are serious concerns over how equal moral treatment plays into an international system of human rights, I believe moral equality is important enough (at least by virtue of its effects) to garner widespread support among nations and serve as a useful lens for human rights practitioners.